1995
DOI: 10.1007/bf00141600
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and toxicity of sediment-bound lead to a filter-feeder bivalve Crassostrea gigas (Thunberg)

Abstract: Two different approaches were used to study the bioavailability of sediment-bound lead. In vitro techniques simulating the potential metal desorption under conditions prevailing in the digestive tract were assayed on a contaminated sediment. An experimental model of a food chain was designed to determine the retention of lead in the soft tissues of oysters according to the environmental source of the metal (water or sediment). Neither enzymatic action nor leaching at low pH (both aspects of digestion) induce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…However, this potential bioavailability is only responsible for a low additional As accumulation in the soft tissues of oysters, contrary to previous observations about Cu and Pb transfer from sediment (Ettajani et al 1992;Amiard et al 1995). On the other hand, when As is provided with phytoplanktonic food, incorporation has been observed in marine invertebrates of the Chesapeake Bay and the Baltic Sea but no food-chain biomagnification was apparent (Sanders et al 1989;and unpublished results by Notini and Rosemarin (1986) mentioned in the previous reference).…”
Section: Discussioncontrasting
confidence: 73%
“…However, this potential bioavailability is only responsible for a low additional As accumulation in the soft tissues of oysters, contrary to previous observations about Cu and Pb transfer from sediment (Ettajani et al 1992;Amiard et al 1995). On the other hand, when As is provided with phytoplanktonic food, incorporation has been observed in marine invertebrates of the Chesapeake Bay and the Baltic Sea but no food-chain biomagnification was apparent (Sanders et al 1989;and unpublished results by Notini and Rosemarin (1986) mentioned in the previous reference).…”
Section: Discussioncontrasting
confidence: 73%
“…Fichet et al (1999) observed that meiofauna, and nematodes in particular, may be an important route for metal transfer from sediment to organisms through the food web. Although the release of bioavailable metals represents a risk to the biota (Amiard et al 1995), only a relatively limited number of meiofaunal and foraminiferal microand mesocosm experiments have been conducted on heavy metals (e.g., Austen and McEvoy 1997;Gustafsson et al 2000;Ernst et al 2006;Gyedu-Ababio and Baird 2006;Hedfi et al 2007;Mahmoudi et al 2007;Hermi et al 2009;Beyrem et al 2011;Boufahja et al 2011;Frontalini and Coccioni 2012;Frontalini et al 2018), and only a few of these studies focused on the effects of Pb (i.e., Austen and McEvoy 1997;Millward et al 2001;Gyedu-Ababio and Baird 2006;Mahmoudi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the fraction of sediment-bound metal readily bioavailable, in vitro studies have been proposed (Luoma and Bryan, 1978;Bourgoin et al, 1991;Amiard et al, 1995). However, the mobility shown even in realistic conditions provides only an assessment of potential bioavailability.…”
Section: Introductionmentioning
confidence: 99%